Role of zinc-methionine chelate on bone health and eggshell quality in late–phase laying hens - A.D. Niknia; R. Vakili; A.M. Tahmasbi (All Life, 2023)
This experiment aimed to assessing bone status and eggshell properties of laying hens at the end of a production cycle in response to inclusion of zinc-methionine chelate and zinc sulfate to diet. In a completely randomized design, 125 Leghorn laying hens (w36) 80 weeks old were divided into five treatment groups with five replications.Treatments were control (without zinc supplementation), zinc sulfate treatments (30 and 45 mg/kg), and zinc-methionine chelate (30 and 45 mg/kg). There was a significant increase in the feed intake in zinc sulfate and zinc -methionine chelate treatments campare the control treatment (P < 0.05). Tibia ash was significantly higher in treatments containing sulfate and zinc methionine chelate than in the control treatment (P < 0.05). The tibia's cortical thickness was improved in laying hens receiving 30 mg/kg zinc-methionine chelate. The supplementation of zinc could lead to an increase of mineralization in bone tissue. According to the results, zinc supplementation can improve feed intake, egg weight and the optimal zinc absorption in tissues. Zinc-methionine chelate boosts tibial mechanical properties without compromising eggshell quality of laying hens at the end of a production cycle.